ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KTP-ELEKTRONIK DI KECAMATAN AEK NATAS - ARTHA LUMBAN TOBING (JURNAL ILMIAH KOHESI, 2021)
This research is descriptive quantitative with the aim to measure significant Public Satisfaction Towards KTP-ElektronikServices. The data used in this study are primary data and secondary data. Primary data was obtained through thedissemination of questionnaires with the number of respondents as many as 91 people and secondary data obtained fromthe district agency Aek Natas. Data analysis using Multiple Regression Data (SPSS version 22). Data analysis using multipleregression, hypothesis test and coefficient of determination test with signification level of 95% (α=0.05). Based on theanalysis of data that has been done, obtained the following results: (1) The influence of public satisfaction on KTP-el servicesis 70.9%. (2) the coefficient of multiple regression of service procedures shall be 4,265. the requirement regression coefisiesis 3,483. coefisies the regression of officer clarity of 3,150. coefisies of officer discipline regression of 3,026. coefisiesregression of officer capability of 2,047. coefisies regression service speed of 1,060 . coefisies regression of courtesy andfriendliness of officers by 1,028. coefisies of regression of service comfort of 0.149. The most influential public satisfactionwith KTP-el services is the service procedure. This can be seen from the value of the variable regression coefficient ofservice procedures greater than the requirements, clarity of officers, discipline of officers, ability of officers, speed of service,courtesy and friendliness of officers, comfort of service. From the results of the above analysis concluded that an evaluationof public satisfaction affects the service of KTP-el.